Unveiling Prophetic Maqashid in Hadiths about Rahn - Hardivizon, Hardivizon; Shalihin, Nurus; Wendry, Novizal (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This article delved into the interplay between hadiths related to rahn (pledge or collateral) and the prophetic maqashid within the framework of Islamic finance. Addressing the gaps in existing literature, the research employs qualitative methods, combining hadith criticism and Hassan Hanafi's hermeneutics framework. Three main themes emerge: the permissibility of rahn, the utilization of rahn property, and the prohibition of owning rahn property. Hadiths regarding the permissibility of rahn showcase Prophet Muhammad's practical application of Islamic principles in economic transactions, emphasizing justice, ethical business practices, and leadership involvement. Hadiths on the utilization of rahn property emphasize compensation, tolerance, and ethical treatment of animals, aligning with Islamic values in economic activities. The prohibition of owning rahn property hadith establishes fundamental principles of justice, equality, and the protection of individual rights in economic transactions. The article concluded that these hadiths not only serve as legal guidance but also embody prophetic maqashid, contributing to the broader goals of Islam to create a just and balanced society, particularly in economics and finance. The comprehensive framework provided by these hadiths offers valuable insights for both academics and practitioners navigating the evolving landscape of Islamic finance, addressing contemporary challenges while upholding Islamic values